Ucapan Terima Kasih Tim Editor JAL Vol. 6, No. 2, Oktober 2020 - JAL, Pengelola (Jurnal Arsitektur Lansekap; Vol.6, No.2, Oktober 2020, 2020)
Ucapan Terima Kasih Tim Editor JAL Vol. 6, No. 2, Oktober 2020